The practice of halal and toyyib principles among migrant food handlers IIUM food services: a food safety and hygiene perspective through a mixed-methods approach - Saiful Nazri, Aina Syahira; Mahamad Maifiah, Mohd Hafidz (IIUM Press, 2026)
Food service establishments in universities serve as the primary dining destinations for students, where the principles of halal and toyyib become significant considerations in maintaining overall hygiene and safety within food production and processing environments. However, ensuring adherence to these principles has become critical, particularly when migrant workers are involved in food handling. Despite their significant contribution to food service operations, limited research has examined their compliance with halal, hygiene, and food safety practices. The objective of this study was to assess the level of compliance with halal and toyyib principles among migrant food handlers at the International Islamic University Malaysia (IIUM), Gombak, about food safety and hygiene practices. This study also aimed to identify the factors contributing to non-adherence to these practices. A mixed-method approach was employed, combining quantitative and qualitative data collection. A structured questionnaire was distributed to 30 migrant food handlers, and 10 respondents were selected for in-depth interviews to gain deeper insights into the factors influencing their practices. Data were analysed using descriptive analysis and Creswell’s five-step method. The results revealed that 73.3% of respondents demonstrated high compliance, with an overall mean score of 4.32 on a 5-point Likert scale. However, specific weaknesses were identified in key areas, including protecting food from contamination, properly thawing food, and using thermometers for temperature control. Additionally, the findings identified four factors contributing to non-compliance, including limited training, poor attitudes, operational and resource constraints, and differing cultural or religious perspectives. Although overall adherence to the practices is excellent, targeted improvements are needed to address the identified gaps. This highlights the necessity of continuous awareness and training initiatives that account for the cultural and linguistic diversity among migrant groups, as well as the implementation of rules and monitoring systems to ensure the integrity of halal food consumed